A simplified herbal formula for the treatment of heart failure: Efficacy, bioactive ingredients, and mechanisms. (September 2019) - Chen, Zixin; Luo, Tong; Zhang, Lu; Zhou, Zheng; Huang, Yusheng; Lu, Lu; Yang, Zhongqi; Wang, Lingjun; Xian, Shaoxiang
Graphical abstract: Abstract: Heart failure (HF) is a complex pathology for which single-agent therapy cannot provide comprehensive efficacy. Therefore, effective combination therapies for HF are increasingly emphasized. Multiple-component drugs derived from Chinese herbal formulae provide efficacy and safety when administered to patients with HF. Nuanxinkang (NXK) is a simplified Chinese herbal formula which has been widely applied in HF for decades. It exhibits comprehensive cardiac protective effects in HF patients as an adjuvant therapy, including improving heart function and quality-of-life, reducing inflammation, and regulating neurohormones. Nevertheless, the bioactive ingredients and mechanisms of action of NXK are unknown, which hinders its further application. Here, we examined the therapeutic efficacy of NXK in a mouse model of HF. Using transcriptome analysis and drug similarity analysis we found that NXK inhibits apoptosis and inflammation, while improving cardiac contraction and reversing myocardial fibrosis. In addition, we detected 21 bioactive species in NXK using UHPLC-MS analysis. Based on these data, we performed network pharmacology analysis to investigate ingredient-target-pathway interactions. We further confirmed 13 genes as potential targets, and assessed the effects of NXK on the AKT to validate the anti-apoptotic role of NXK both in vivo and in vitro . Thus, our work has identified a simplified herbal formula with efficacy against HF by exploring its constituents and mechanism of action, providing evidence for an innovative treatment strategy and novel therapeutic targets for HF.